Back up your entire network. - Rose, Scott
Time Machine is great for backing up one or two Macs, but when backing up a larger network og Macs, it's better to use a more sophisticated backup program that gives you more control over the process. Your best best for powerful network backup software is the combination of ChronoSync and ChronoAgent (www.econtechnologies.com). Together, these applications give you almost unlimited flexibility for scheduling backups, backing up multiple sources to multiple destinations, creating bootable backups, and more. You'll also get enterprise-level features like central management of you backups from a single Mac, email notification of errors, and detailed backup logs. These instructions will help you set up one "server" Mac to back up any number of "client" Mac home folders to an external hard drive attached to the server Mac.
Keywords: Macintosh (Computer); Electronic data processing -- Backup processing alternatives; Mac OS 10.3.; Servers; Backup; ChronoAgent; Time Machine; Networking; Network backup software